Outcome of the consultation with Member States and EFSA on the basic substance application for approval of vinegar for the extension of use in plant protection as a herbicide for non‐agricultural areas. Issue 12 (19th December 2019) - ,
Abstract : The European Food Safety Authority (EFSA) was asked by the European Commission to provide scientific assistance with respect to the evaluation of applications received by the European Commission concerning basic substances. In this context, EFSA's scientific views on the specific points raised during the commenting phase conducted with Member States and EFSA on the basic substance application for an extension of use for vinegar are presented. The context of the evaluation was that required by the European Commission in accordance with Article 23 of Regulation (EC) No 1107/2009 following the submission of an application for approval of vinegar as a basic substance for an extension of use in plant protection as a herbicide for non‐agricultural areas. The current report summarises the outcome of the consultation process organised by EFSA and presents EFSA's scientific views on the individual comments received.